Effect of Physical and Chemical Mutagens on Seedling Thaits of Berseem (Trifolium Alexandrinum L.) - Jatasra, D J; Chhabra, A K; Kharb, R P.S (Annals of Arid Zone, 2016)
The effect of ethyl methyl sulphonate (EMS) and gamma-rays + EMS onseedling traits of three berseem cultivars was investigated during 1983 and 1984. The cv Mescavi had highest germination and recorded maximum root length and shoot Itngth. EMS alone affected germination more than the combination of gamma-rays + EMS. The treatments with EMS (0.5% and 0.75%1 proved most effective for increasing root and shoot lengths.